2010
DOI: 10.1097/bot.0b013e3181d7a0aa
|View full text |Cite
|
Sign up to set email alerts
|

Objective CT-Based Metrics of Articular Fracture Severity to Assess Risk for Posttraumatic Osteoarthritis

Abstract: Objectives Intra-articular fractures predispose patients to post-traumatic osteoarthritis (PTOA), with associated chronic joint pain and decreased function. The success of articular fracture management is dependent on how the fracture is treated and on fracture type and severity. The purpose of the present study was to correlate objective CT-based indices of intra-articular fracture severity with subsequent joint degeneration. It was hypothesized that an injury severity metric that included objective measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 11 publications
0
56
1
1
Order By: Relevance
“…Prior research on inflammatory cytokine concentrations between high-and lowenergy injuries demonstrated no difference [19]. In a study using CT-based metrics, Thomas et al [44]found that both fracture energy and articular comminution combined served as a better predictor of eventual development of posttraumatic OA than each individual component alone. The Schatzker classification does not account for articular comminution, and the presence of articular comminution may be more indicative of some elements of fracture energy than condylar involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research on inflammatory cytokine concentrations between high-and lowenergy injuries demonstrated no difference [19]. In a study using CT-based metrics, Thomas et al [44]found that both fracture energy and articular comminution combined served as a better predictor of eventual development of posttraumatic OA than each individual component alone. The Schatzker classification does not account for articular comminution, and the presence of articular comminution may be more indicative of some elements of fracture energy than condylar involvement.…”
Section: Discussionmentioning
confidence: 99%
“…The current technique does not permit discriminating the energy absorption directly associated with bony fracture versus these non-fracture factors. (Imaging techniques for estimating bone fracture energy from CT-based assessment of de novo inter-fragmentary free surface area have recently been developed [20], but are outside the scope of the present study.) However, the present survival experiment results indicate that, at least in this range of impaction parameters for this particular surgical preparation, delivered energy is clearly not a sufficient measure of the energy actually absorbed in creating tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in injury severity assessment following fractures of the tibial plafond in human patients suggest that increasing levels of both energy of injury as well as increasing fracture area in the joint are predictive of developing PTA without considering reduction [17]. These same authors also found a critical threshold for residual articular displacement over which the development of PTA was more likely [10].…”
Section: Etiology Of Post-traumatic Arthritismentioning
confidence: 98%
“…Furthermore, recent studies suggest that battlefield orthopaedic injuries represent the majority of long term disability in wounded soldiers in on-going military conflicts, and degenerative arthritis developing following injury is the most common reason for a wounded soldier to be considered unfit for return to duty [6]. Recent developments in injury severity assessment suggest that increasing fracture involvement of the articular surface may be predictive of developing PTA in humans [17]. The unique features of intra-articular fractures include impaction injury to the articular surface, disruption of the osteochondral composite layer, residual displacement of the articular surface, and exposure of the joint to blood and marrow contents.…”
Section: Introductionmentioning
confidence: 99%